PERMINTAAN KONSUMEN TERHADAP BERAS DI PASAR BERSEHATI KOTA MANADO - Demiyanti Umawaitina; Ribka M. Kumaat; Yolanda P.I. Rori (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research isÂ  to examine consumer demand for rice at the Manado City Besehati Market. This research was conducted at the BersehatiÂ  Market Manado City. The study lasted for 3 months starting from one week of data collection to the preparation of research reports. This study uses primary data and secondary data where primary data is obtained through direct interviews with respondents in Bersehati markets based on questionnaires in the form of questionnaires while secondary data in this study comes from books available at local internet bookstores such as Google Scholar to access articles from various journals scientific and thesis from Elementary and other universities related to consumer demand for rice. The sampling method is accidental sampling. The respondents were consumers who met at retailers in a Bersehati market as many as 60 consumers, taken from each of the rice retailers in the Manado health market. The demand for rice in the Bersehati Market varies from the type and for Superwin Kota, the price was Rp. 10.000-12.000/ kg). The rice that is most in demand by consumers is the city Superwin rice as much as 136 kilograms or 44.44% of the total rice purchased, because besides the price varies, and the quality is good and tastes good. The demand for rice is at least 2 kilograms or 0.65% of the total rice purchased.Keywords: Demand for rice, Bersehati Market, Manado City